Religious Otherness and National Identity in Scandinavia, c. 1790-1960 The Construction of Jews, Mormons, and Jesuits as Anti-Citizens and Enemies of Society - Ulvund, Frode (Religious Minorities in the North, 2020)
The book addresses how certain religious groups were labeled as foreign and constructed as political, moral and national threats in Scandinavia between c. 1790 and 1960. Key questions are who articulated such opinions, how was the threat depicted, and to what extent did it influence state policies towards these groups. The author also discusses how the inimical images of religious minorities influenced the construction of national identities.